Percepção, processamento e treinamento auditivo musical com usuários de implante coclear - Scheila Farias de Paiva Lima (2010)
Introduction: Currently, cochlear implant (CI) constitutes the most effective way to treat profound hearing loss. Also known as the bionic ear, the IC is a prosthesis surgically inserted in the inner ear to promote auditory stimulation in subjects with profound bilateral sensorineural hearing loss. Currently, much has advanced the technology of IC and its forms of sound processing have shown excellent benefits. Although there are many studies concerning about the benefits of IC for speechn perception, music perception still constitutes a vast field of study for professionals in the area and at the same time, one of the biggest challenges for implant users. This research investigates the relationship between the perception of oral language and music perception in adults with post-lingual hearing loss and cochlear implant users based on the parameters of frequency and duration used in the programming of speech coding strategies and sound processing equipment in Colear Implant (CI). Objectives: To evaluate the performance of CI users for the tasks of assessment and musical training related to discrimination and recognition of time (frequency) and duration and also to describe the perceptual process-musical adult CI users for recognition of musical elements tasks in music appreciation. Methodology: This is a case study of design descriptive, non-probabilistic sampling defined by type, consisting of two adults with hearing loss post-lingual cochlear implant users, the first one is a 68-aged male, Multichannel Cochlear Implant user for two years and six months, model ® PULSAR CI100 and speech processor Opus I Medel ® brand and the other one is a 47-aged female, post-lingual deaf, cochlear implant user for 8 years, Nucleus 22 model and as a component external the speech processor Freedom Cochlear ® brand. The research adopts a qualitative approach experimental where perceptual changes musicals presented by the individuals studied may be observed from the records and hearing evaluations performed for the music appreciation. The first stage consisted of applying a questionnaire to the auditory-musical history. An assessment Auditory Processing and an application of standard tests of duration and frequency - FPT and DPT were done. The second part was an intervention through a music auditory training program based on appreciation of music, and at the third stage the evaluation applied at the first stage was done again and also a qualitative data analysis about the evaluation of participants performance during activities of appreciation and auditory training in music, as well as the proposed program. The results after the training showed an evolution in the music hearing development as well as the effectiveness of the assessment and auditory training in music program.